2007
DOI: 10.1103/physrevb.75.041304
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport in a two-dimensional electron system in dc electric fields

Abstract: We report on nonequilibrium transport measurements in a high-mobility two-dimensional electron system subject to weak magnetic field and dc excitation. Detailed study of dc-induced magneto-oscillations, first observed by Yang et al., reveals a resonant condition that is qualitatively different from that reported earlier. In addition, we observe dramatic reduction of resistance induced by a weak dc field in the regime of separated Landau levels. These results demonstrate similarity of transport phenomena in dc-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
143
4
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 17 publications
16
143
4
1
Order By: Relevance
“…[14]. Another notable nonlinear effect: strong reduction of the longitudinal resistance by the dc electric field has been observed at considerably smaller biases [15,16,17]. In the paper [16] the strong reduction of the resistance has been attributed to substantial changes of the electron distribution function induced by the DC electric field E dc .…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…[14]. Another notable nonlinear effect: strong reduction of the longitudinal resistance by the dc electric field has been observed at considerably smaller biases [15,16,17]. In the paper [16] the strong reduction of the resistance has been attributed to substantial changes of the electron distribution function induced by the DC electric field E dc .…”
mentioning
confidence: 89%
“…It was found that the microwave radiation makes the response to the dc electric field to be more linear. Strongly nonlinear I-V curves were observed in this experiment, however, the transition to the zero differential resistance state has not been detected (see also recent experiments [15,16,17]). We suggest that the lower electron mobility in our samples can be the possible reason of the stronger nonlinearity.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, the oscillatory behavior in the nonlinear magnetotransport has attracted much attention: in a 2D system even without irradiation, a relatively weak current can induce drastic suppression and strong oscillations of the differential magnetoresistance, and may result in a state of zero-differential resistance. 22,23,24,25,26 Several theoretical models have been proposed in an attempt to explain this interesting nonlinear phenomenon. 27,28,29,30 Numerical examinations based on the current-control transport scheme were shown in good agreement with the experimental observation for differential magnetoresistivity as a function of the ratio of the current density to the magnetic field in both the magnetic-field sweeping and the current-sweeping configurations covering both separated and overlapping Landau level regimes.…”
mentioning
confidence: 99%